CYP1A1 m1 and m2 polymorphisms: genetic susceptibility to lung cancer - Mota,Paula (2010)
Lung cancer is considered an environment-related disease that develops as a consequence of exposure to mutagenic agents, namely those present in tobacco. The CYP1A1 gene codifies the phase I enzyme aryl hydrocarbon hydroxilase (AHH) belonging to the cytochrome P450 system that plays a major role in the bio-activation of tobacco procarcinogenes. Two CYP1A1 polymorphisms, m1 (T6235C transition) and m2 (A4889G transition), are associated with greater enzymatic activity and have been described as genetic susceptibility factors for lung cancer. The aim of this study was to verify if this association holds true in blood samples of 175 lung cancer patients and 217 non-cancer patients from Portugals midlands region. The samples were studied by restriction fragment length polymorphism (RFLP) assay. The allelic frequencies of the mutant alleles were 0.12 for allele C and 1.14 for allele G in the control population. The results were not statistically different from those alleles in the patient population. There was also no statistically significant difference in genotype distribution in lung cancer patients and controls even when combining high risk genotypes. In our control sample, as in other populations of different ethnic origin, both polymorphisms also seem to be in linkage disequilibrium. We conclude that in this sample of the Portuguese population, CYP1A1 m1 and m2 polymorphisms are too rare to be of clinical relevance, and do not seem to be associated with susceptibility to lung cancer.